The preference of Bitcoin and stocks in Indonesia - Novi Swandari Budiarso; Winston Pontoh (Yayasan Widyantara Nawasena Raharja, 2022)
Bitcoin is an alternative and is currently in demand by investors. This condition triggers investors' preferences to invest in stocks or cryptocurrencies. This study examines the causality between Bitcoin and the market index in Indonesia in terms of determining the preferences of investors. On this objective, the sample is taken from 1 January 2022 to 31 October 2022. The findings of this study imply that investors' preferences tend to be caused by stock price movements. But, the result of estimation also finds that the preference of investors tends to be influenced by the movement of Bitcoin.